EFEKTIFITAS PROGRAM KAMPUNG SIAGA BENCANA DI DESA BULUBETE KECAMATAN DOLO SELATAN KABUPATEN SIGI - Zulkarnain, Zulkarnain (Katalogis, 2015)
This research aims at determining the effectiveness of the Disaster-Prepared Village Program in the village of Bulubete, Southern Dolo, District of Sigi. This is a qualitative research with descriptive method. The informants of this research are the employees of Social Department, the program implementers and the people who were determined by using purposive sampling technique. The techniques of the data collection include observations, interviews, and documentations, while the technique of data analysis refers to the stage of Miles and Huberman which consists of three activities that occur simultaneously: data reduction, data presentation, drawing conclusions / verification. The results showed that the effectiveness of the program in Disaster-Prepared Village Program in the village of Bulubete is not effective, due to the goal optimization has not run as expected, due to the lack of planning and supervision carried out in disaster management. In the case of a system perspective, Disaster-Prepared Village Program has not run based on implementation guidelines, such as the lack of sections in charge of the evacuation, field kitchen, transportation, health, shelter and logistics. As well as the pressure on the behavior of members of the Disaster-Prepared Village has not shown totality because they have not shown their preparedness and the lack of KSB's roles in disaster relief because there are sections that must be run by its members.